Réponses

2013-11-20T12:20:30+01:00
A = 3(1/4+x)-1/4
A = (3/4)+3x-(1/4)
A = 3x+(1/2)
A = (6x+1)/2

B = 2/3x + 5(x-1/6)
B = (2/3)x+5x-(5/6)
B = (17/3)x-(5/6)
B = (34x-5)/6

C = 3/4(x-5)+ 1/2
C = (3/4)x-(15/4)+(1/2)
C = (3/4)x-(13/4)
C = (3x-13)/4

D = 2+ 3(1/5x-1/3)
D = 2+(3/5x)-1
D = (3+5x)/5x
2013-11-20T12:40:21+01:00
A= 3(1/4+x)-1/4
=3/4+3x-1/4
=3x+2/4
=3x+1/2

B= 2/3x + 5(x-1/6)
=2/3x+5x-5/6
=2/3x+15/3x-5/6
=17x/3-5/6

C= 3/4(x-5)+ 1/2
=3x/4-15/4+1/2
=3x/4-15/4+2/4
=3x/4-13/4

D= 2+ 3(1/5x-1/3)
=2+3/5x-3/3
=2+3/5x-1
=3/5x+1